Pedagogi, Andragogi, dan Pendidikan Agama Kristen - Gaol, Nasib Tua Lumban (Sekolah Tinggi Teologi Kanaan Nusantara, 2019)
Learning approach is the important part of Christian Religious Education that needs to pay attention seriously in order to achieve the aim of learning. This study is purposed to explore the concept of pedagogy and andragogy, and then analyze them with Christian religios education. Pedagogy and andragogy approach are very necessary for educator in learning process. Therefore, the future study should be conducted for supporting the betterment practice of Christian education.